2020
DOI: 10.1111/psyp.13566
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting ADJUST: Optimizing the ADJUST algorithm for pediatric data using geodesic nets

Abstract: A major challenge for electroencephalograph (EEG) studies on pediatric populations is that large amounts of data are lost due to artifacts (e.g., movement and blinks). Independent component analysis (ICA) can separate artifactual and neural activity, allowing researchers to remove such artifactual activity and retain a greater percentage of EEG data for analyses. However, manual identification of artifactual components is time‐consuming and requires subjective judgment. Automated algorithms, like ADJUST and IC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 19 publications
1
66
0
Order By: Relevance
“…The copyright holder for this preprint (which this version posted May 23, 2021. ; https://doi.org/10.1101/2021.05.21.445085 doi: bioRxiv preprint thus, it is possible that other available methods, like adjusted-ADJUST (Leach et al, 2020), may provide better performance. One possible explanation is that these methods are not optimal for infant data due to the intrinsic properties of the signal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The copyright holder for this preprint (which this version posted May 23, 2021. ; https://doi.org/10.1101/2021.05.21.445085 doi: bioRxiv preprint thus, it is possible that other available methods, like adjusted-ADJUST (Leach et al, 2020), may provide better performance. One possible explanation is that these methods are not optimal for infant data due to the intrinsic properties of the signal.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some algorithms have been adapted for infant data. For example, the ADJUST algorithm (Mognon et al, 2011) has been adapted into the adjusted-ADJUTS (Leach et al, 2020), and the MARA algorithm (Winkler et al, 2011) into iMARA (Marriot Haresign et al, 2021). While these modified algorithms work better on infant data, they rely on optimizations done on adult training sets.…”
Section: Independent Component Analysismentioning
confidence: 99%
“…ICA weights from the ICA run on the copied (1 Hz) dataset were then copied back to the continuous 0.3 Hz high-passed data. The adjusted-ADJUST Matlab scripts ( Leach et al, 2020 ; Mognon et al, 2011 ) identified artifactual independent components, which were then removed from the data. The data were epoched from −1000 ms before to 2000 ms after both the cue and the stimulus.…”
Section: Methodsmentioning
confidence: 99%
“…During data collection, electrodes were referenced to electrode Cz. All pre-processing, including ocular artifact detection and removal, was performed with the Maryland Analysis of Developmental EEG (MADE) pipeline (Debnath et al, 2020), which utilizes MATLAB (The MathWorks, Natick, MA) functions from EEGLAB (Delorme & Makeig, 2004) and its plugins “FASTER” (Nolan et al, 2010), “ADJUST” (Mognon et al, 2011), and “ADJUSTED ADJUST” (Leach et al, 2020). Offline, data were re-referenced to an average reference and band-pass filtered from 0.3 to 50 Hz with a digital FIR filter.…”
Section: Methodsmentioning
confidence: 99%